Primary atomization of liquid jets: Identification and investigation of droplets at the instant of their formation using direct numerical simulation. (March 2023) - Trautner, Elias; Hasslberger, Josef; Ketterl, Sebastian; Klein, Markus
Abstract: A detailed investigation of droplet characteristics for the primary atomization of a round liquid jet injected into stagnant gas is performed using direct numerical simulation. The material properties correspond to a Diesel injection, and the numerical framework is based on the volume-of-fluid method. The study is carried out in the statistically steady state, which allows to collect time-averaged droplet formation statistics. A novel algorithm continuously detects droplets at the instant they detach from the liquid core jet, which are referred to as primary droplets. The main droplet characteristics, such as volume, velocity and sphericity, are captured for newly formed primary droplets as well as all other droplets in the domain. This allows a detailed comparison between droplet characteristics during and after their formation. In addition, the droplet Weber, Reynolds and Stokes numbers are computed. These dimensionless numbers govern important physical processes occurring subsequent to the droplet formation, such as potential secondary breakup and droplet motion. One central goal is to provide information relevant for large eddy simulation of sprays in the Eulerian–Lagrangian framework, where the formation of small droplets from the liquid core jet cannot be resolved, and therefore potentially needs to be modeled. Moreover, the relative importance of primary and secondary atomization is estimated for this specific setup. It is found that the distribution of the droplet sizes is very similar for primary droplets and the entire droplet collective. Furthermore, the droplet Weber numbers are significantly below the critical Weber number required for secondary droplet breakup. Together, these two observations indicate that, for the investigated configuration, primary atomization is the dominating process, while secondary atomization only plays a minor role. Moreover, the high droplet volume fraction observed shows that droplet–droplet collisions and coalescence can be expected to influence the spray behavior. To put the obtained results into perspective, empirical correlations for the Sauter Mean Diameter are used to discuss potential trends for higher Reynolds and Weber numbers. Highlights: Direct numerical simulation of the primary atomization of a round liquid jet. Novel tracking algorithm detects droplets detaching from the liquid core jet. Comparison of the newly formed droplets and the entire droplet collective. Primary atomization has a strong influence on the droplet size spectrum. Droplet coalescence is expected to influence the droplet size spectrum. Secondary atomization plays no significant role.